PENERAPAN SISTEM INLISLITE VERSI 3.2 DALAM MENINGKATKAN EFISIENSI LAYANAN PERPUSTAKAAN DI INDONESIA - Wirawan, I Dewa Agung Satriya; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 4 No 2 (2024), 2025)
The implementation of INLISLite Version 3.2 aims to enhance library services in Indonesia, especially at the National Library of Indonesia. This research evaluates the efficiency improvements brought by INLISLite 3.2, focusing on user satisfaction and library management. The study uses a mixed-method approach, collecting quantitative data from user surveys and qualitative data from interviews with librarians. The results show significant improvements in cataloging processes, data management, and user experience.